Vocational High School Teacher's Work Ethic - Sitanggang, Nathanael; Luthan, Putri Lynna Adelinna (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
Essential research describes the work ethic of Vocational High School teachers and the indicator that mostly affects the formation of the latent variable of the vocational teacher's work ethic. The research used a survey method with a sample consisting of 212 SMK teachers in Medan. The analytical technique used was a confirmatory factor analysis with SEM analysis using AMOS tools. The analysis revealed that the SMK teachers’ work ethic reached 35.85%, categorised as high, 52.36% as adequate, 8.49% as inadequate, and 3.30% as low. It also showed that an indicator variable of having a preference for working hard served as the strongest indicator (52.70%) that formed the latent construct variable of the vocational teachers' work ethic. Subsequently, the latent construct variables of vocational teachers' work ethic contain several indicators that include a preference for working hard at 52.70%; willingness to give more than required at 50.55%; fairness at 49.14%; willingness to cooperate at 48.86%; working honestly with 42.64%; work efficiently during working hours with 39.18%; and respecting colleagues with 25.60%.